2020
DOI: 10.1016/j.yexmp.2020.104409
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrosis and decreased connexin 43 in rat hearts after exposure to high-intensity infrasound

Abstract: Background: Noise is an important environmental risk factor. Industrial environments are rich in high-intensity infrasound (hi-IFS), which we have found to induce myocardial and coronary perivascular fibrosis in rats. The effects of exposure to IFS on the ventricles have been studied, but not on the atria. We hypothesized that rats exposed to hi-IFS develop atrial remodeling involving fibrosis and connexin 43, which we sought to evaluate. Material and methods: Seventy-two Wistar rats, half exposed to hi-IFS (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…The loss of bladder function is similar to the symptoms of IC in humans [ 5 , 19 ]. Increased collagen in the interstitium and muscle layer indicates interstitium and muscle layer fibrosis and loss of bladder contraction ability [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of bladder function is similar to the symptoms of IC in humans [ 5 , 19 ]. Increased collagen in the interstitium and muscle layer indicates interstitium and muscle layer fibrosis and loss of bladder contraction ability [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the direct effects of high-intensity infrasound in tissues, other exposure animal studies showed that continuous exposure results in proliferation of collagen fibers and tissue fibrosis 12 , 13 . Several authors suggest that the body vibrations and resonance produced by high-intensity infrasound represents a mechanical stimulus that activates intracellular signaling pathways resulting in extracellular matrix remodeling and fibrosis 6 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For the histochemical analysis of pancreatic islet fibrosis, three random images of equal area containing pancreatic islets were selected from each animal and analyzed using the ImageJ software 56 , as described previously 12 . In short, for each image the pancreatic islets were isolated, and their blue pixel content was measured relative to the total islet area using a color deconvolution method 57 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations